1981
DOI: 10.1107/s0567740881003877
|View full text |Cite
|
Sign up to set email alerts
|

Trirhodium scandium heptasilicide and triiridium scandium heptasilicide with a new rhombohedral structure type

Abstract: Abstract. ScRh3SiT: a = 7.5056 (6), c = 19.691 (4)/k, D x = 5.706 Mg m -3,/l(Mo Ka) = 9.6 mm -1, F(000) = 1524; Sclr3SiT: a = 7.5010 (2), c = 19.909 (1)/k, Dx = 8.403 Mg m -3, g(Mo Ka) = 67 mm -1, F(000) = 2100. ScRhaSi 7 and SclraSi7 crystallize with a new rhombohedral structure type in space group R3c, Z = 6. For ScRh3Si 7 (Sclr3SiT) the final R = 0.037 (0.072) for 272 (250) reflections. The Rh and Sc arrangement found in ScRh3Si 7 is similar to that found in the PdFa-type structure. Sc (Pd) are at the centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…This compound crystallizes in the rhombohedral space group R3c (No. 167), isotypic to ScRh 3 Si 7 and ScIr 3 Si 7 [26], and possesses an inversion center. It does not exhibit superconductivity above 1.8 K. We note that thorough investigation of the synthesis of CaPtSi 3 by a flux method by Takeuchi et al, resulted in synthesizing a new centrosymmetric superconductor, Ca 2 Pt 3 Si 5 [27].…”
Section: Appendix A: the New Materials Cair3si7mentioning
confidence: 99%
See 1 more Smart Citation
“…This compound crystallizes in the rhombohedral space group R3c (No. 167), isotypic to ScRh 3 Si 7 and ScIr 3 Si 7 [26], and possesses an inversion center. It does not exhibit superconductivity above 1.8 K. We note that thorough investigation of the synthesis of CaPtSi 3 by a flux method by Takeuchi et al, resulted in synthesizing a new centrosymmetric superconductor, Ca 2 Pt 3 Si 5 [27].…”
Section: Appendix A: the New Materials Cair3si7mentioning
confidence: 99%
“…Since this crystal structure contains a large number of atoms per unit cell in a nontrivial arrangement, it must (1) 2.4449 (7) Ir-Si (1) 2.4526 (7) Ir-Si (1) 2.5201(7) Ir-Ca 3.0697(1) Ca-Si (1) 3.1257 (7) Si(1)-Si (1) 2.5985(13) Si(1)-Si (2) 2.7127(7) Si(1)-Si (1) 2.7365(15) Si(1)-Si (1) 2.7605 (15) be broken into subunits to be described. As ScRh 3 Si 7 , it was portrayed as an array of Sc(Ca)-centered Rh(Ir) octahedra and Si double tetrahedra in which the shared apex was the Si(2) site [26]. However, since the shortest bonds in the material are those between Rh(Ir) and Si, it may be more realistic to visualize the structure in terms of slightly twisted Si-centered Ir 3 Si 7 barrels and isolated Ca atoms.…”
Section: Appendix A: the New Materials Cair3si7mentioning
confidence: 99%
“…Former phase analytical work done by Braun et al [2] in the system ScRh-Si revealed the existence of 9 ternary phases. However, later on only ScRhSi [3], ScRhSi 2 [4], ScRh 3 Si 7 [5] and Sc 5 Rh 4 Si 10 [6] were structurally characterized, the latter only from powder data. Four ternary phases have been reported in the System Sc-Ir-Si, but only the structures of ScIr 3 Si 7 [5] and Sc 5 Ir 4 Si 10 [6] are known from single crystal work.…”
Section: Introductionmentioning
confidence: 99%
“…However, later on only ScRhSi [3], ScRhSi 2 [4], ScRh 3 Si 7 [5] and Sc 5 Rh 4 Si 10 [6] were structurally characterized, the latter only from powder data. Four ternary phases have been reported in the System Sc-Ir-Si, but only the structures of ScIr 3 Si 7 [5] and Sc 5 Ir 4 Si 10 [6] are known from single crystal work. The structures of ScIrSi [3] and Sc 4 Ir 7 Si 6 [7] were assigned on the basis of powder patterns.…”
Section: Introductionmentioning
confidence: 99%
“…In Mg 3 Ir 3 Si 8 15 the truncated tetrahedra are also centered by magnesium atoms, while they are empty in the structure of Mg 5 T 10 Si 16 ( T = Pd, Pt) 16. Silicon tetrahedra, which are corner connected to form Si 7 double tetrahedra are known from the crystal structure of MgIr 3 Si 7 17 (ScRh 3 Si 7 type18).…”
Section: Resultsmentioning
confidence: 99%